2020
DOI: 10.1002/adhm.202001463
|View full text |Cite
|
Sign up to set email alerts
|

One Responsive Stone, Three Birds: Mn(III)‐Hemoporfin Frameworks with Glutathione‐Enhanced Degradation, MRI, and Sonodynamic Therapy

Abstract: Ultrasound-driven sonodynamic therapy (SDT) catches numerous attentions for destroying deep-seated tumors, but its applications suffer from unsatisfactory therapeutic effects and metabolism. Furthermore, SDT is usually weakened by the complex tumor microenvironment, such as the overexpression of glutathione (GSH). To address these issues, Mn(III)hemoporfin frameworks (Mn(III)-HFs) are reported as nanosonosensitizers by using biocompatible hematoporphyrin monomethyl-ether (HMME) to coordinate with Mn(III) ions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 45 publications
(49 reference statements)
0
36
0
Order By: Relevance
“…Under 488 nm light excitation, the fluorescent spectrum of FITC-labeled-CAT@HA-HMME NPs ( Fig. S2d ) is featured with three emission peaks at 518, 613, and 674 nm, which are respectively indexed to FITC (518 nm) and HMME (613 and 674 nm) [ 36 ] characteristic peaks. Meanwhile, the encapsulation capability of CAT was determined by bicinchoninic acid (BCA) protein assay, and it is calculated to be 22.5% ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Under 488 nm light excitation, the fluorescent spectrum of FITC-labeled-CAT@HA-HMME NPs ( Fig. S2d ) is featured with three emission peaks at 518, 613, and 674 nm, which are respectively indexed to FITC (518 nm) and HMME (613 and 674 nm) [ 36 ] characteristic peaks. Meanwhile, the encapsulation capability of CAT was determined by bicinchoninic acid (BCA) protein assay, and it is calculated to be 22.5% ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the TME, the nanoplatform not only acts as an siRNA delivery carrier to realize precise gene therapy but also mediates an excellent CDT effect for the generation of toxic • OH due to the Fenton-like effect of Mn 2+ produced by the degradation of MnO 2 . Intracellular GSH was depleted by MnO 2 to GSH disulfide (GSSG), which promoted the Fenton-like reaction and enhanced the generation of • OH (Figure A). , To investigate the • OH generation ability of the as-synthesized probes on tumor cells, we first designed experiments to evaluate their efficiency of generating Mn 2+ . Different concentrations of GSH solutions were mixed with the as-prepared ErNPs@MnO 2 -RGD solution (1 mmol L –1 of Mn) followed by inductively coupled plasma (ICP) mass spectrometry analysis of the supernatant to obtain a distribution map of Mn 2+ , which showed that Mn 2+ was generated with increasing concentrations of GSH (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…MnCPs were prepared according to our previous report with Mn(OAc) 3 •2H 2 O (30 mg) and HMME (20 mg) as key components. 37 The obtained nanoparticles (MnCPs) were centrifuged and washed with ethyl alcohol and deionized water three times.…”
Section: Methodsmentioning
confidence: 99%